2021
DOI: 10.1371/journal.pone.0255667
|View full text |Cite
|
Sign up to set email alerts
|

Towards a better characterisation of deep-diving whales’ distributions by using prey distribution model outputs?

Abstract: In habitat modelling, environmental variables are assumed to be proxies of lower trophic levels distribution and by extension, of marine top predator distributions. More proximal variables, such as potential prey fields, could refine relationships between top predator distributions and their environment. In situ data on prey distributions are not available over large spatial scales but, a numerical model, the Spatial Ecosystem And POpulation DYnamics Model (SEAPODYM), provides simulations of the biomass and pr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
6
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7
1

Relationship

2
6

Authors

Journals

citations
Cited by 9 publications
(6 citation statements)
references
References 81 publications
(166 reference statements)
0
6
0
Order By: Relevance
“…In addition, other environmental and biological variables could have been considered. Some studies use other variables to study cetacean distribution such as the distribution and concentration of prey species (Pendleton et al, 2020;Virgili et al, 2021) or canyon areas, because submarine canyons are widely recognised as hotspots in cetacean distribution (Tepsich et al, 2014). Pendleton et al (2020) suggested that using modelled prey availability, rather than oceanographic proxies, could be important to forecast species distributions.…”
Section: Model Improvementmentioning
confidence: 99%
“…In addition, other environmental and biological variables could have been considered. Some studies use other variables to study cetacean distribution such as the distribution and concentration of prey species (Pendleton et al, 2020;Virgili et al, 2021) or canyon areas, because submarine canyons are widely recognised as hotspots in cetacean distribution (Tepsich et al, 2014). Pendleton et al (2020) suggested that using modelled prey availability, rather than oceanographic proxies, could be important to forecast species distributions.…”
Section: Model Improvementmentioning
confidence: 99%
“…Some previous studies have used biological predictors related to prey availability in cetacean species distribution models, but results have been inconsistent. In a recent paper, Virgili et al (2021) investigated the use of SEAPODYM micronekton estimates in SDMs of ziphiid beaked whales and sperm whales in the North Atlantic basin. The authors found that these predictors were not selected for the beaked whale model and only marginally improved performance for the sperm whale model.…”
Section: Discussionmentioning
confidence: 99%
“…The addition of deep-water variables alone did not entirely explain the distribution of deep-divers but improved the explanatory power of the models and highlighted other processes that could influence their distribution at depth. More direct parameters such as prey distribution data simulated from numerical models could further improve our distribution models 50 , 51 . However, prey models need refinements to better characterise the prey of deep-diving cetaceans and thus to improve whale distribution models.…”
Section: Discussionmentioning
confidence: 99%